2010
DOI: 10.1007/s00264-010-1176-4
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of bilateral fractures over sixteen years: localisation and variation in treatment of second hip fractures

Abstract: The aim of this study was the evaluation of contralateral hip fractures after a previous hip fracture. For this retrospective analysis patients were selected from the database of the LUMC, a teaching hospital in the south-west of the Netherlands. We analyzed all patients with a second fracture of a hip between 1992 and 2007. The exclusion criteria were high impact trauma and patients with diseases or medication known to have a negative effect on bone metabolism. A total of 1,604 hip fractures were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
(26 reference statements)
4
8
0
1
Order By: Relevance
“…We found that the risk of another fracture among survivors increased steadily with time, reaching 34% by 10 years, and did not differ between women and men after adjustment for age, fracture type, period, and hospital length of stay. Our findings on the rate and cumulative incidence of events are in agreement with previous reports [5,17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In particular, we confirm that women have higher rates of second hip fracture during the early post-injury periods and lower death rates overall, when compared to men.…”
Section: Discussionsupporting
confidence: 95%
“…We found that the risk of another fracture among survivors increased steadily with time, reaching 34% by 10 years, and did not differ between women and men after adjustment for age, fracture type, period, and hospital length of stay. Our findings on the rate and cumulative incidence of events are in agreement with previous reports [5,17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In particular, we confirm that women have higher rates of second hip fracture during the early post-injury periods and lower death rates overall, when compared to men.…”
Section: Discussionsupporting
confidence: 95%
“…This is in line with literature data, where intervals from 2 to 5 years between the first and second hip fracture are reported (2,4,6). Given this short period, substantial changes in patient characteristics were not very likely.…”
Section: Discussionsupporting
confidence: 90%
“…A first hip fracture is a risk factor for sustaining a second hip fracture at the contralateral side. Other reported predictors for a second hip fracture include age, female gender, living alone, alcoholism, any prior fracture, functional status, dementia, and osteoporosis (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the risk factors; the role of accompanying diseases, bone status, body mass index, residence, Singh index, localization of the fracture, physical functioning, and complications are often studied. [2][3][4]7,8] On the other hand, little is known about the effect of different settlement types (location of residence) and operation techniques of primary fractures as risk factors of second hip fractures.…”
Section: Risk Factors Of Subsequent Contralateral Hip Fracturesmentioning
confidence: 99%